A pilot study to assess the sensitivity and specificity of an intrasound device in the diagnosis of ankle fractures. Issue 4 (July 1997) - Dancocks, A; Rouse, A; Hiscox, J
Abstract : OBJECTIVE: To investigate the use of a simple intrasound device in the detection of malleolar fractures in the accident and emergency (A&E) department. METHODS: Patients aged 16 to 70 years with ankle injuries presenting within 24 hours were considered for inclusion in the study. Those patients with bony tenderness, inability to weight bear, and swelling were examined with a simple intrasound device before x-ray examination. A positive result of discomfort, pain, withdrawal response, or combinations or these was noted. RESULTS: The device had a sensitivity of 85% and a specificity of 52% in detecting malleolar fractures. CONCLUSIONS: The use of intrasound in the detection of malleolar fractures cannot be relied upon alone, but it may help to limit the number of x rays taken unnecessarily. A further study is proposed to confirm these findings.